The effect of applying the problem-based learning model on the mathematical problem-solving ability of grade X students at MAS Madinatussalam, Sei Rotan Village - Ersandi Lazuardi; Asmin Asmin (Edumaspul: Jurnal Pendidikan, 2025)
This research was conducted with the aim of: (1) knowing the differences in students' mathematical abilities before and after being given treatment using the Problem Based Learning (PBL) learning model, (2) knowing the effect of the Problem Based Learning learning model on students' mathematical problem solving abilities, (3) knowing the differences in students' mathematical problem solving abilities taught with the Problem Based Learning learning model and the Conventional learning model, (4) knowing how the students' answer process was in the Problem Based Learning class posttest, with a pretest-posttest design. The research subjects were 30 students, and the learning was carried out in four meetings. The data collection methods used were through pretest and posttest of students' mathematical problem solving abilities, observation of teacher activities, and observation of student activities. The results of the study showed that: (1) the results of the Paired Sample t-test showed that the calculated t-value (4.352) > t-table (1.697) and the Sig. value. (0.000) < (0.05, then H0 is rejected and H1 is accepted, meaning there is an average difference in students' mathematical problem solving abilities before and after the PBL model is applied. (2) the results of the simple linear regression test obtained a Sig. value (0.000) < (0.05) and t-count (4.779) < t-table (1.697), H0is rejected and H1 is accepted, meaning that the Problem Based Learning learning model has a significant effect on students' mathematical problem solving abilities, (3) the results of the independent sample t-test can be seen from the calculated t value (8.501) > t table (1.697) and the Sg. value (0.001) < (0.05), then H0is rejected and H1 is accepted, meaning there is an average difference in the final (posttest) mathematical problem solving abilities of students in the Problem Based Learning class and the Conventional class, (4) the process of students' answers in the final test with the PBL model shows that the category of students' problem-solving abilities in the final test is already in the very good category, this can be seen from the average post-test score of the PBL class which is 90. Therefore, it is recommended for mathematics teachers to use the Problem Based Learning learning model as an effort to improve students' mathematical problem-solving abilities.